VIDEO COMPANY PROFIL SEBAGAI MEDIA PROMOSI UNTUK MENINGKATKAN KEPERCAYAAN MASYARAKAT TERHADAP PRODUK EMAS CV.GANDA MULIA UNGARAN - Didik Wijaksono; Andik Prakasa Hadi (STEKOM PRESS, 2016)
CV. Ganda Mulia is a business entity engaged in the production and sale of various gold and jewelery, especially gold bars which are used as an investment CV. Ganda Mulia is a newly developing company, and already has a variety of media used to promote, but a sense of interest and public trust in the CV. Ganda Mulia has not been maximized, so we need a complementary promotion that can attract and even provide a sense of confidence in the confidence of gold bars, especially used as an investment. Therefore the writer tries to develop a complementary promotional media as a means of promoting the CV. Ganda Mulia that already exists, which is used to increase trust and a sense of interest in gold products CV. Double Majesty. With complementary media in the form of a company profile video, it contains the benefits, benefits and the production process or the process of making gold bars. So that when people understand the benefits and advantages of investing in gold bullion, it will have a positive impact, which is about trust and interest in gold products CV. Double Majesty. In the manufacturing process the author uses the RnD method, the results of this research in the form of a video company profile CV. Ganda Mulia Ungaran which has been uploaded on diyoutube, on the CV website. Ganda Mulia at the address www.gandamulia.com, and burned into a CD in the form of a DVD format that is used as an archive and is also used when there are company activities in the form of exhibitions or the like. hardware and software that supports the creation and editing of a company profile video.